Scientific approach in table tennis and tennis in Slovenia - Kondric, Miran; FIlipcic, Ales (Ontario, Canada Sport Books Publisher, 2009)
This academic monograph presents the results of researchers done at the University of Ljubljana, faculty of sport, Slovenia. The expansion of sports science together with the commercialization of table tennis and tennis in recent years have directed attention on improved performance. This has led to a more detailed study and understanding of all aspects of the two games. Racket sports, especially table tennis and tennis, have also posed a unique challenges to scientists and have provided means for developing scientific methodology. The present monograph is based upon the authors' long practical and theoretical experience and generalization of the achievements in projecting long-term training programme in table tennis and tennis. This book addresses sports scientists, coaches, athletes, pedagogues, students of physical education and higher education institutions of sport, faculties of physical education and kinesiology
1. Comparison of injuries between top Slovenian table tennis players and top Slovenian tennis and badminton players -- 2. Myoelectric comparison of table tennis forehand stroke using different ball sizes -- 3. Physiological anaerobic characteristics of Slovenian elite table tennis players -- 4. Differences in grf executing forehand topspin with different balls -- 5. Kinematic analysis of top spin stroke with balls of two different sizes -- 6. Possibilities to reduce speed and spin by changing the thickness of sandwich rubber -- 7. The expert system for orientation of children into table tennis in the Republic of Slovenia -- 8. Computer supported system for the evaluation of fitness of Slovenian youth table tennis players -- 9. Injuries in tennis from the aspect of training factors -- 10. Correlation of tennis motor skills and basic anthropometric characteristics and its influence on the competition successfulness of young tennis players -- 11. Regression analysis of tennis-specific motor abilities and the competition efficiency of young female tennis players -- 12. Comparison of distance covered between young male and female tennis players -- 13. Comparison of parents' and coaches' behaviour towards male and female tennis players in different ages -- 14. Reliable and valid tests in tennis -- 15. Time and game analysis at the men's grans slam tennis tournaments finals -- 16. Comparative analysis of time, playing and movement factors between two different quality groups of wheelchair tennis players -- 17. Analysis of time characteristics in wheelchair tennis -- 18. Stroke analysis in wheelchair tennis -- 19. Relation between two aerobic capacity tests and competitive successfulness of junior tennis players
Includes bibliographical references and index
Keywords: Tennis -- Slovenia; Table tennis -- Slovenia